A novel BH3 mimetic efficiently induces apoptosis in melanoma cells through direct binding to anti‐apoptotic Bcl‐2 family proteins, including phosphorylated Mcl‐1. (18th December 2014) - Liu, Yubo; Xie, Mingzhou; Song, Ting; Sheng, Hongkun; Yu, Xiaoyan; Zhang, Zhichao
Summary The Bcl‐2 family modulates sensitivity to chemotherapy in many cancers, including melanoma, in which the RAS/BRAF/MEK/ERK pathway is constitutively activated. Mcl‐1, a major anti‐apoptotic protein in the Bcl‐2 family, is extensively expressed in melanoma and contributes to melanoma's well‐documented chemoresistance. Here, we provide the first evidence that Mcl‐1 phosphorylation at T163 by ERK1/2 and JNK is associated with the resistance of melanoma cell lines to the existing BH3 mimetics gossypol, S1 and ABT‐737, and a novel anti‐apoptotic mechanism of phosphorylated Mcl‐1 (pMcl‐1) is revealed. pMcl‐1 antagonized the known BH3 mimetics by sequestering pro‐apoptotic proteins that were released from Bcl‐2/Mcl‐1. Furthermore, an anthraquinone BH3 mimetic, compound 6, was identified to be the first small molecule to that induces endogenous apoptosis in melanoma cells by directly binding Bcl‐2, Mcl‐1, and pMcl‐1 and disrupting the heterodimers of these proteins. Although compound 6 induced upregulation of the pro‐apoptotic protein Noxa, its apoptotic induction was independent of Noxa. These data reveal the promising therapeutic potential of targeting pMcl‐1 to treat melanoma. Compound 6 is therefore a potent drug that targets pMcl‐1 in melanoma.